Bridging the digital divide: mathematics teachers’ perceptions and use of information and communication technologies in the classroom at secondary schools in Tanzania - Chuma, Furaha; Raphael, Christina (Papers in Education and Development, 2025)
This research investigated the perceptions of lower secondary school mathematics teachers regarding the use of Information and Communication Technology (ICT) in instruction. Ten ordinary secondary schools from Dar es Salaam and five from the Coastal regions were involved in the study. The schools were chosen based on their Mathematics Grade Point Average (GPA) from the 2021 Form Four National examinations. The research used a mixed methods approach whereby data were gathered through semi-structured interviews and questionnaires. Data were analysed using the SPSS IBM 25 software. Drawing upon the Technology Acceptance Model (TAM), it was deduced that teachers’ perceptions of the usefulness and user-friendliness of ICT tools played a significant role in their adoption. Therefore, this study recommends collaborative efforts between policymakers and educators to fully leverage the benefits of integrating ICTs in mathematics education, ultimately serving both mathematics teachers and students for enhancing teaching and learning processes and quality of education.